THEORETICAL FACTORS OF INNOVATIVE ACTIVITY (British Journal of Global Ecology and Sustainable Development, 2023)
The current educational development brought a new direction - innovative pedagogy to the field. In this article, the conditions for the formation of the teacher's innovative activity, the formation of the teacher's creative individuality are discussed information about the dynamic innovation processes of development and renewal.